Development of an Instructional Model based on Science, Technology, Society and the Environment Perspectives and Empirical Evidence to Enhance Student Teachers’ Understanding and Teaching of Nature of Science - Somsak Gathong (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The research and development aimed 1) to survey the nature of science understanding of the students in Bachelor of Education Program, 2) to develop the instructional model based on Science, Technology, Society and Environment (STSE) perspectives with the emphasis of the empirical evidence of the student teachers, 3) to study the results of the instruction model application in constructing the student teachers’ understanding related to the nature of science, and 4) to develop and improve the instructional model based on Science, Technology, Society and Environment (STSE) perspectives the emphasis of the empirical evidence of the student teachers. The research methodology included 4 phases reflecting the research and development (R&D) as Phase 1: research is fundamental information analysis for the development of the instructional model with samples including 23 student teachers and 3 instruments for data collection i.e. Phase 1 is the research as the analysis of basic information for the instructional model development with 3 research instruments as 1) a survey on the nature of science understanding among the students 2) a form of content analysis, and 3) a questionnaire on environmental awareness the students and all of them were analyzed by content analysis, the index of Item Objective Congruence (IOC) assessment, mean and standard deviation. Phase 2 is the development of the instructional model with the target group of 1) 5 experts specializing in the instructional model validation to analyze data with the content analysis, the index of Item Objective Congruence (IOC) assessment, mean and standard deviation; and Phase 3 is the experimental application of the instructional model with 3 research instrument as 1) a survey on the nature of science understanding 2) a form of learning management plan analysis, and 3) a questionnaire on satisfaction towards the instructional model application. The data were analyzed by mean, standard deviation, Phase 3 is the experimental application of the instructional model with 3 research instrument as 1) a survey on the nature of science understanding 2) a form of learning management plan analysis, and 3) a questionnaire on satisfaction towards the instructional model application. The data were analyzed by mean, standard deviation and t-test, and Phase 4 is the evaluation and improvement of the instructional model. The findings can be concluded as follows; 1. The result of measuring the nature of science understanding was found that the student teachers understood the nature of science at a moderate level and scientific issues had the empirical evidence was at a low level. 2. The developed instruction model consisted of the principles, objectives, instructional processes, knowledge and skill, social system, the principles of response and support which having instructional process comprised of 6 steps as follows: Step 1: Engagement, Step 2: Exploration, Step 3: Evidence-based practice, Step 4: Reflection, Step 5: Implementation and Publication, and Step 6: Evaluation. The consistency investigation result of the instructional model based on Science, Technology, Society, and Environment perspectives with the emphasis of the empirical evidence was 0.85 which was consistent. 3. The experimental results in applying the instructional model revealed that the nature of science understanding after applying the instructional model was higher than before applying it statistically significant at .01 level. The satisfaction towards the application Science, Technology, Society, and Environment perspectives with the empirical evidence instructional model showed that the student teachers had the most satisfaction and the satisfaction towards the instructional model found that the student teachers applied the Implicit Approach for the nature of science instruction. 4. The evaluation and improvement of the instructional model to enhance its efficiency could be achieved by the improvement of seeking empirical evidence and developing the Explicit Approach together with Reflection and Coaching and Mentoring for further instruction development with effectiveness.